2017
DOI: 10.3390/molecules22020209
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Quercetin, a Polyphenol, on Blood Pressure

Abstract: Disorder of blood pressure control causes serious diseases in the cardiovascular system. This review focuses on the anti-hypertensive action of quercetin, a flavonoid, which is one of the polyphenols characterized as the compounds containing large multiples of phenol structural units, by varying the values of various blood pressure regulatory factors, such as vascular compliance, peripheral vascular resistance, and total blood volume via anti-inflammatory and anti-oxidant actions. In addition to the anti-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
93
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(96 citation statements)
references
References 75 publications
1
93
0
2
Order By: Relevance
“…In recent years, quercetin has become a rising concern in nutritional and therapeutic potential, owning to its multiple pharmacological effects (Russo, Spagnuolo, Tedesco, Bilotto, & Russo, ). In addition to antitumor, antiobesity, antihypertensive, and significant heart‐related benefits, a large number of in vivo studies have shown that quercetin had a strong potential for antidiabetes and its complications (Bule, Abdurahman, Nikfar, Abdollahi, & Amini, ; Hu et al, ; Lu et al, ; Marunaka et al, ; Patel et al, ; Shi et al, ; Y. Zhao et al, ; X. Zhu, Cheng, et al, ; Y. Zhu, Teng, et al, ). It has been found that quercetin prevents diabetes mellitus by decreasing blood glucose via enhancing insulin sensitivity and stimulating insulin secretion from β cells (Gaballah, Zakaria, Mwafy, Tahoon, & Ebeid, ; Jeong, Kang, Choi, Kim, & Kim, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, quercetin has become a rising concern in nutritional and therapeutic potential, owning to its multiple pharmacological effects (Russo, Spagnuolo, Tedesco, Bilotto, & Russo, ). In addition to antitumor, antiobesity, antihypertensive, and significant heart‐related benefits, a large number of in vivo studies have shown that quercetin had a strong potential for antidiabetes and its complications (Bule, Abdurahman, Nikfar, Abdollahi, & Amini, ; Hu et al, ; Lu et al, ; Marunaka et al, ; Patel et al, ; Shi et al, ; Y. Zhao et al, ; X. Zhu, Cheng, et al, ; Y. Zhu, Teng, et al, ). It has been found that quercetin prevents diabetes mellitus by decreasing blood glucose via enhancing insulin sensitivity and stimulating insulin secretion from β cells (Gaballah, Zakaria, Mwafy, Tahoon, & Ebeid, ; Jeong, Kang, Choi, Kim, & Kim, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, quercetin has become a rising concern in nutritional and therapeutic potential, owning to its multiple pharmacological effects (Russo, Spagnuolo, Tedesco, Bilotto, & Russo, 2012). In addition to antitumor, antiobesity, antihypertensive, and significant heart-related benefits, a large number of in vivo studies have shown that quercetin had a strong potential for antidiabetes and its complications (Bule, Abdurahman, Nikfar, Abdollahi, & Amini, 2019;Hu et al, 2017;Lu et al, 2015;Marunaka et al, 2017;Patel et al, 2018;Shi et al, 2019;Y. Zhao et al, 2017;X.…”
mentioning
confidence: 99%
“…Quercetin is a plant flavonol of the flavonoid polyphenol group found in many fruits, vegetables, leaves, and grains [21][22][23]. Although numerous studies have demonstrated that quercetin plays a role in the prevention of various cancers [24][25][26], it is still an interesting target for OSCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin is a major dietary flavonoid notably present in onions, apples, teas or berries (Figure b). Many studies have been conducted on its pharmacokinetics, bioavailability, its potential effects on health, multidrug resistance or blood pressure . Many clinical studies have been conducted to investigate the fate of quercetin after being ingested as aglycone, as glycosides or a combination of both .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on its pharmacokinetics, [18] bioavailability, [19] its potential effects on health, [20] multidrug resistance [21] or blood pressure. [22] Many clinical studies have been conducted to investigate the fate of quercetin after being ingested as aglycone, [23,24] as glycosides [25][26][27] or a combination of both. [28] Studies have also been performed using cooked onions [29][30][31] or tomato juice [32] as a quercetin source.…”
Section: Introductionmentioning
confidence: 99%